2004
DOI: 10.1002/col.20071
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the visibility of low-contrast color Landolt-Cs: Effect of aging human lens

Abstract: We measured response time, the number of nonresponses, response error, and subjective visibility evaluation for color Landolt-Cs with a gray color background presented on a CRT display to young and old adults (mean ages: 22.3 and 65.9 years, respectively)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 12 publications
3
20
0
Order By: Relevance
“…The experiment involved 4 young and 3 elderly subjects who joined in the previous experiment (Suzuki et al, 2005). We confirmed that all subjects had normal color vision using the Tokyo Medical College Color Vision Test (Murakami Color Res.…”
Section: Subjectsmentioning
confidence: 80%
See 2 more Smart Citations
“…The experiment involved 4 young and 3 elderly subjects who joined in the previous experiment (Suzuki et al, 2005). We confirmed that all subjects had normal color vision using the Tokyo Medical College Color Vision Test (Murakami Color Res.…”
Section: Subjectsmentioning
confidence: 80%
“…The stimuli and test procedures were exactly as described in the previous experiment (Suzuki et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that the yellowing of a human lens affects the color vision of the elderly, and a yellow filter worn by young subjects could simulate the visibility of the elderly [10]. Aging decreases the visibility of color targets [10] as well as the ability of chromatic discrimination compared to young subjects [15]. Despite the extensive research on the relationship between aging and the changes in the lens, most studies focused on the changes themselves, not on the influence of that change to the elderly.…”
Section: Introductionmentioning
confidence: 98%
“…Among the many characteristics of an aging eye, one of the most significant changes is the distorted color appearance in the range of blue and purple [1][2][3][4][5][6]. Although the ocular system, retina, optic nerve, and brain stage also affect the aging of the eyes to some degree [7][8][9][10][11], many studies that have examined the relationship between aging and color vision reported that the lens is the major element known to affect aging [2,4]. Increasing the optical density of a crystalline lens causes changes in light transmittance through the eyes, and as the lens yellows with age, it absorbs a larger amount of short wavelength light in the visible spectrum between 450-470 nm [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%